PENYELESAIAN MASALAH TRANSSHIPMENT DENGAN METODE PERBAIKAN ASM DAN REVISED DISTRIBUTION - FEBRIANTI, ANNISAA’; TASTRAWATI, NI KETUT TARI; SARI, KARTIKA (E-Jurnal Matematika; Vol 11 No 4 (2022), 2022)
One example of transportation problems is the Shvan Art Shop, which is engaged in exporting 20 cm rattan bags. In distributing rattan bags, Shvan Art Shop does not directly send goods to their destination, but still through intermediaries. To overcome this problem, a transshipment model can be used to get a distribution line so that the outgoing costs are minimal. The purpose of this study is to compare distribution costs before applying the transshipment model with after applying the transshipment model using the ASM Repair and Revised Distribution methods. The results showed that the Revised Distribution method resulted in a distribution cost that was less than the Revised ASM method, which was Rp. 42,884,288.00.